The pattern of healthy diets and zero hunger among households in South-West Nigeria: application of linear approximation to quadratic almost ideal demand system - Ogunleke, Ayodeji Oluwaseun; Olawuyi, Seyi Olalekan; Ijila, Olusegun Jeremiah (Frontiers in Public Health, 2023)
Malnutrition and food insecurity remain a significant public health challenge globally, affecting millions of people, particularly in low- and middle-income countries. In Nigeria, the prevalence of malnutrition and food insecurity is high, with a significant burden in the South-West region. Despite several interventions aimed at promoting healthy diets and reducing food insecurity, little is known about the pattern of healthy diets and zero hunger among households, as well as the budget shares on the food items driving these outcomes. Therefore, this study x-rays the pattern of healthy diets and zero hunger among households in South-West Nigeria, using the primary data elicited from 600 rice consuming households, drawn through a multi-stage random sampling technique. Descriptive statistics and Linear Approximation to Quadratic Almost Ideal Demand System (LA-QUAIDS) model were used to analyse the dataset. The estimated LA-QUAIDS model was helpful to decipher the relationships that may not be possible to discover using a single-equation model. The finding of this study revealed that rice, especially local (Ofada) rice is the most consumed food item among the households in the study area with monthly budget share of 0.195. This is an indication that households spend about 19.5% of their monthly food-expenditure share on rice consumption. The results also indicated that yam flour (-0.10), cassava-gari (-2.12) and meat (-0.03) are net complements to rice, while the rest of the food items are regarded as net substitutes. The estimated compensated (-1.64) and uncompensated (-1.69) own price elasticities of local rice respectively indicate that local rice variety is price inelastic and the estimated expenditure elasticity (0.02) suggests that local rice is not a luxury food in the households food basket but a necessity. This study affirms the importance of locally produced foods especially local rice to the households in the study area. In the light of the findings, the study recommends that adequate policy aimed at reducing the cost of local food production, by boosting domestic production. Apparently, this will technically trigger market price adjustment, as shown in this study where local rice was estimated to be own-price elastic in nature.